Air Cargo Capacity on Cargo Terminal Development Plan at Soekarno-Hatta International Airport - P. Ricardianto, Ricky; Kuntohadi, Hendro; Rifni, Muhammad (STMT Trisakti, 2014)
The purpose of this study was to find out the capacity of cargo volume, the needs of cargo warehouse space and utilization in 2023. The writer used quantitative analysis method with linier regression analysis method and a simple least squares method to calculate and forecast the cargo capacity at the amount needs. The calculation of the amount of cargo volume has been projected from the counting of 2010 to 2023, where the amount of desired cargo volume which was approximately 1,500,000 tons can be achieved around the year 2022 to 2023, while the amount of cargo volume at this time in 2013, reaching about 741,000 tons. In 2014 a new warehouse or domestic and international cargo terminal should be built to expand the space of the warehouse so that the old cargo terminal at IA terminal can be replaced. Keywords: air cargo capacity, the cargo warehouse space, warehouse utilization.